STRATEGI PENGENTASAN KEMISKINAN DI PROVINSI ACEH DENGAN MODEL AS-SYATIBI DAN IBNU KHALDUN - Anshari, Al; ArioPutra, Fakhri Muhammad (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
Poverty remains a fundamental issue hindering sustainable development in many regions, including Aceh Province, Indonesia. Despite various poverty alleviation programs, the poverty rate in Aceh remains high, reaching 14.23% in 2024, compared to DKI Jakarta's 4.14%. This study aims to analyze poverty alleviation strategies in Aceh by integrating the models of As-Syatibi and Ibnu Khaldun, which emphasize Islamic values and structural-economic approaches. Using a qualitative descriptive method with library research, this study examines secondary data from BPS reports, academic journals, and Islamic economic development literature. The findings suggest that a holistic strategy combining As-Syatibi's Maqashid Syariah (focusing on the protection of religion, life, intellect, lineage, and wealth) and Ibnu Khaldun's principles of justice, productivity, and state facilitation can effectively address poverty. Recommendations include empowering local communities through Islamic microfinance, education, skills training, and equitable resource distribution, leveraging Aceh's strong Islamic cultural identity for sustainable development.Keywords : Aceh Province, As-Syatibi , Ibnu Khaldun, Islamic economics, Poverty Alleviation